PROPELLING SEPARATISM INTO TRANSNATIONAL SPACES: A CRITICAL ANALYSIS ON THE PRO-LTTE TAMIL DIASPORA IN CANADA - Sanjeewani, D.G.Niruka (UI Scholars Hub, 2024)
Despite being less discussed, the transnational spaces of diaspora communities are often used by terror groups to achieve their ideological and political targets. Their projection of separatist claims in association with terrorist groups threatens not only the territorial control of the home state but also the security and immigration policies of the host state. Linked to these scopes, pro-Liberation Tigers of Tamil Elam (LTTE) diaspora in Canada serving as a case study in this paper to illustrate the dissemination of its separatist ideologies. In addition, this paper also analyses the current rhetoric of the Tamil diaspora for ‘federalism’ that has caused ambiguities about how and to what extent it may impact the territorial structure of Sri Lanka.